Fossil Asterozoa (Echinodermata) of Argentina - Martínez, Sergio (2015)
Thefossil Asterozoa of Argentina have received scant attention. Marine rocks of Early Devonian-Late Miocene age yield ten species of Asterozoa (four Asteroidea and six Ophiuroidea), including the new Neogene record of Astropecten sp. presently introduced. Due to homonymy, Marginix nomen novum is proposed as a substitution of Marginura (Ophiuroidea, Encrinasteridae)